Pengaruh Gaya Hidup dan E-WOM Terhadap Keputusan Pembelian Sepeda di Magelang Selama Pandemi Covid-19 - Muhammad Rohman; Diesyana Ajeng Pramesti (Borobudur Management Review, 2022)
The purpose of this study was to determine the relationship between lifestyle and E-WOM on purchasing decisions. The sample used in this study were bicycle consumers in Magelang during the Covid-19 pandemic. The sampling method is purposive sampling with a lot of 100 respondents. The analysis tool uses multiple regression with the help of SPSS 26.0 software. The results of this study are lifestyle and E-WOM have a simultaneous effect on purchasing decisions, lifestyles have a negative effect on purchasing decisions, E-WOM has a negative effect on purchasing decisions.